Report of five cases of ventricular septal defect (VSD) after acute myocardial infarction in Shahid Beheshti Hospital, Babol, 1994-2004 - MT Salehi Omran (Babol University of Medical Sciences, 2005)
Background and Objective: Ventricular septal defect (VSD) is one of the mechanical complications after acute myocardial infarction (AMI). VSD was recognized by color Doppler echocardiography. The aim of this report was early diagnosis of this complication after AMI with echocardiography and its relation with thrombolytic therapy. Case: The first patient was a 54 year old man who presented to emergency ward with chest pain and he was admitted to CCU with diagnosis of acute anterior AMI and received streptokinase therapy (SK), he had a systolic murmur with thrill in LSB (Left sternal border) and had moderate size muscular VSD with echocardiography. Second patient was 66 year old women who presented which chest pain and she was admitted to CCU with diagnosis of inferior MI and anterior ischemia at distance. She had pansystolic murmur with thrill at LSB and had muscular type VSD with echocardiography. 3rd and 4th and 5th patients who were 75, 80 and 52 years old, respectively were referred with chest pain and with diagnosis of AMI, they had systolic murmur with thrill at LSB, diagnosis of VSD after AMI was confirmed with echocardiography and 5th patient received SK. Selective coronary angiography, cardiac catheterization and oxymetry were done. Conclusion: VSD is one of important complication of AMI. They were recognized with physical examination and echocardiography. Thrombolytic therapy accelerates the time from AMI to VSD formation.